LAW OF SPORT AND ATHLETE FOOTBALL PROFESSIONAL - Tomy Michael; Antonius Feninlambir (Perspektif, 2015)
Kemakmuran atlet sepak bola professional atau karyawan, adalah hak setiap karyawan. Merupakan tanggung jawab organisasi profesional sepak bola untuk bekerja dengan menjamin kesehatan dan keselamatan. Organisasi profesional sepak bola memiliki tanggung jawab penuh dalam hal ini. Melalui penelitian hukum normatif, hasil yang diperoleh disana adalah tidak ada korelasi antara hukum positif di Negara Kesatuan Republik Indonesia dan undang-undang yang dibuat oleh FIFA. Organisasi klub sepak bola profesional tidak benar-benar dijalankan dalam Undang-Undang Nomor 13 tahun 2003, Pasal 87 pada tenaga kerja dimana setiap perusahaan harus menerapkan kesehatan dan keselamatan sistem manajemen terintegrasi dan sistem manajemen kesehatan. Oleh karena itu diperlukan aturan hukum yang selaras dengan peraturan yang dibuat oleh FIFA, PSSI dihormati untuk peraturan di Indonesia yang berhubungan dengan olahraga yang melakukan tidak ada kontradiksi sebelum diterbitkan undang-undang organisasi, sehingga acara pengunduran diri atlet profesional sepak bola di masa depan, harus memperhitungkan isi dari kontrak mereka.Prosperity of athlete football professional or employees is the right of every employees. The responsibility of the organization of professional football clubs to occupational with their health and safety. Organization of professional football clubs have full responsibility in this regard. With normative legal research. The result obtained there is no correlation between positive of law in Unity State Republic of Indonesia and the statuten made by FIFA. Organization of professional football clubs have not been absolutly run in Law of Republic of Indonesia No. 13 of 2003, Article 87 on labour in which every company must implement a health and safety of management system integrated working with the health management system. As a suggestion, require the rule of law which is in sync with the regulations made by FIFA, PSSI respected to the regulations in Indonesia related to sports that do not event of contradiction before publish the statuten of the organization so that no event of resignation athlete professional football in the future, they shall take into account the contennt of their contract, the public take an active role in infraction notice made by PSSI or other organizations professional football clubs on the regulation of professional football athlete contract that have been made, and the researchers of science of law are examining the country’s sovereignty and the sovereignty of FIFA.